How to {make} things {be } or {do }: modelling danish, swedish, and bulgarian object control and object predicative structures - Radoev, Konstantin (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The article presents a synchronic, contrastive, generative X-bar model of Danish, Swedish, and Bulgarian causative and resultative structures of the object control and object predicative types in the context of language interference among Bulgarian students with L2s such as English, German and other widely-spoken European languages studied in Bulgarian high schools. Via a semantic role-based way to model corpus examples in parallel in the three languages, an argument is made that providing a parallel with Bulgarian would be a more effective way to teach the difference between these constructions.